2019
DOI: 10.1017/s1355617719000985
|View full text |Cite
|
Sign up to set email alerts
|

Use of Neuroimaging to Inform Optimal Neurocognitive Criteria for Detecting HIV-Associated Brain Abnormalities

Abstract: Objective:Frascati international research criteria for HIV-associated neurocognitive disorders (HAND) are controversial; some investigators have argued that Frascati criteria are too liberal, resulting in a high false positive rate. Meyer et al. recommended more conservative revisions to HAND criteria, including exploring other commonly used methodologies for neurocognitive impairment (NCI) in HIV including the global deficit score (GDS). This study compares NCI classifications by Frascati, Meyer, and GDS meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Even with the success of combination antiretroviral therapy (cART), various neurological complications caused by the infiltration of the human immunodeficiency virus (HIV) in the central nervous system (CNS) (1), especially HIV-associated neurocognitive disorder (2), remain a heavy disease burden. Neuroimaging is a vital tool to provide insight into structural, functional, and molecular changes occurring in the brain and has the potential to comprehensively elucidate the pathogenesis of HIV-associated neurocognitive disorder (3,4). Structural magnetic resonance imaging (sMRI) studies of HIV-infected (HIV+) individuals have found widespread brain atrophy and volume reduction in the subcortical structures including caudate nucleus, putamen, amygdala, thalamus, hippocampus, and parahippocampus (5)(6)(7)(8), and cerebellar (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Even with the success of combination antiretroviral therapy (cART), various neurological complications caused by the infiltration of the human immunodeficiency virus (HIV) in the central nervous system (CNS) (1), especially HIV-associated neurocognitive disorder (2), remain a heavy disease burden. Neuroimaging is a vital tool to provide insight into structural, functional, and molecular changes occurring in the brain and has the potential to comprehensively elucidate the pathogenesis of HIV-associated neurocognitive disorder (3,4). Structural magnetic resonance imaging (sMRI) studies of HIV-infected (HIV+) individuals have found widespread brain atrophy and volume reduction in the subcortical structures including caudate nucleus, putamen, amygdala, thalamus, hippocampus, and parahippocampus (5)(6)(7)(8), and cerebellar (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging is a promising approach to assess brain morphometric and functional changes that shows broad application prospects in the diagnosis and management of PLWH and may have the potential to shed light on the pathogenesis of HAND ( Clifford and Ances, 2013 ; Saylor et al, 2016 ; Campbell et al, 2019 ). Previous structural MRI studies indicated that PLWH display widespread brain atrophy in the subcortical nucleus as well as the frontal, parietal, occipital, temporal, and cerebellar cortices and cortical thinning in the frontal and temporal lobes and cingulate cortex ( Wilson et al, 2015 ; Underwood et al, 2017 ; Sanford et al, 2018a , b ; Israel et al, 2019 ; Hassanzadeh-Behbahani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with more limited test batteries show inconsistent findings and are likely to misclassify rates of HIV-related neurocognitive impairment and/or decline. This issue of misclassification is compounded when impairment is defined by low performance in a single domain (increased false positive rate) or when more stringent impairment thresholds of 1.5 or 2 SD below the mean are applied (increased false negative rate) despite evidence that a -1 SD cutoff optimally balances sensitivity and specificity for HIV-related CNS injury (Campbell et al, 2020;Cherner et al, 2002;Saloner & Cysique, 2017).…”
Section: Hiv-associated Neurocognitive Disordermentioning
confidence: 99%